2023
DOI: 10.3390/biology12040581
|View full text |Cite
|
Sign up to set email alerts
|

SPEADI: Accelerated Analysis of IDP-Ion Interactions from MD-Trajectories

Abstract: The disordered nature of Intrinsically Disordered Proteins (IDPs) makes their structural ensembles particularly susceptible to changes in chemical environmental conditions, often leading to an alteration of their normal functions. A Radial Distribution Function (RDF) is considered a standard method for characterizing the chemical environment surrounding particles during atomistic simulations, commonly averaged over an entire or part of a trajectory. Given their high structural variability, such averaged inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…Understanding the relationship between the monomer conformational transformations underlying nucleation and subsequent oligomerization, and how these relate to the disease, is pivotal to the development of aggregation inhibitors 21 . Thus, various all-atom [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and coarse-grained (CG) 37,[40][41][42][43][44][45][46][47][48][49] molecular simulations studies were reported on the structure of the monomer and small oligomers of α-syn. Table S1 provides details on the models and systems studied in these works.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the relationship between the monomer conformational transformations underlying nucleation and subsequent oligomerization, and how these relate to the disease, is pivotal to the development of aggregation inhibitors 21 . Thus, various all-atom [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and coarse-grained (CG) 37,[40][41][42][43][44][45][46][47][48][49] molecular simulations studies were reported on the structure of the monomer and small oligomers of α-syn. Table S1 provides details on the models and systems studied in these works.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the relationship between the monomer conformational transformations underlying nucleation and subsequent oligomerization and how these relate to the disease is pivotal to the development of aggregation inhibitors . Thus, various all-atom and coarse-grained (CG) , molecular simulations studies were reported on the structure of the monomer and small oligomers of α-syn. Table S1 provides details on the models and systems studied in these works.…”
Section: Introductionmentioning
confidence: 99%